A simple manual rosetting method for absolute CD4+lymphocyte counting in resource-limited countries - Phonethipsavanh Nouanthong (2018)
A CD4 monoclonal antibody which reacts with CD4+lymphocytes but does not react significantly with monocytes was generated and used to develop a simple method for CD4 count. In a comparison with standard flow cytometry, high correlation was obtained. The developed method can be an alternative to flow cytometry for resource-limited countries. Copyright © 2006, American Society for Microbiology. All Rights Reserved.